2016
DOI: 10.1016/j.jclepro.2016.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Direct electric curing of alkali-activated fly ash concretes: a tool for wider utilization of fly ashes

Abstract: Utilization of the fly ashes is a major problem in many developing countries and in South Africa only about 7% of the fly ash produced annually by coal-fired power stations, has being utilized. Although, fly ashes can be used as an alternative binder in alkali-activated concretes, strength development of these concretes at room temperature is slow limiting application of the material. Direct electric curing is proposed for heat curing of alkali-activated fly ash concrete which will open new opportunities for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Bakharev (2005) [28] observed that fly ashes activated with NaOH had more stable strength properties at later ages than fly ashes activated with sodium silicate. Previous work revealed that the NaOH present in the alkali activator provided an adequate conductive medium for generating heat in accelerated curing of NaOH-activated fly ash concretes [29].…”
Section: The Limitations Encountered During the Heated Plate Curing Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakharev (2005) [28] observed that fly ashes activated with NaOH had more stable strength properties at later ages than fly ashes activated with sodium silicate. Previous work revealed that the NaOH present in the alkali activator provided an adequate conductive medium for generating heat in accelerated curing of NaOH-activated fly ash concretes [29].…”
Section: The Limitations Encountered During the Heated Plate Curing Tmentioning
confidence: 99%
“…The electric current will induce the heating mechanism (Joule heating [29] and taking part in the alkali activation of fly ash [35]. There is a critical range for the conductivity of the alkaline solution in order for Joule heating to be effective.…”
Section: Response Variable and Variable Level Selectionmentioning
confidence: 99%
“…Fly ash is a by-product from coal combustion, however the demand for fly ash as a construction material is increasing. Nonetheless, there are still many countries where efficient utilisation of fly ash is a major problem with as little as 7% being used effectively [25]. Slag is a by-product of steel manufacture and is produced when blast furnace slag is cooled rapidly in water resulting in glassy granules, these are then ground to form a fine powder [26].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, 70% of the PFA produced in the UK was used in the manufacture of construction materials [21]. Nonetheless there are approximately 114 million tonnes of PFA stockpiled accessibly in the UK [22] and in many countries around the world utilisation of PFA is a major problem with as little as 7% being utilised effectively [23].…”
Section: Introductionmentioning
confidence: 99%